2005
DOI: 10.1080/17402520500303339
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Mesenteric Lymph Node T Cell Phenotype and Cytokine Secretion are Associated with Changes in Thymocyte Phenotype after LP‐BM5 Retrovirus Infection

Abstract: In this study, mouse MLN cells and thymocytes from advanced stages of LP-BM5 retrovirus infection were studied. A decrease in the percentage of IL-7 þ cells and an increase in the percentage of IL-16 þ cells in the MLN indicated that secretion of these cytokines was also altered after LP-BM5 infection. The percentage of MLN T cells expressing IL-7 receptors was significantly reduced, while the percentage of MLN T cells expressing TNFR-p75 and of B cells expressing TNFR-p55 increased. Simultaneous analysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Normally, CD8 T cells in WT mice expand to reach a peak burst size at day 8, after which they enter a decay phase after complete clearance of the virus (27), whereas in the KO mice the defects in activation and proliferation of cytotoxic cells may delay viral clearance, which might explain a higher proportion of residual effector cells in the lymph nodes, in contrast to WT mice. Additionally, it has also been reported that MLN T cells could present abnormal phenotypes under viral infection (28). Is also important to remark that Srsf1-cKO mice have a disrupted naïve to effector/ effector memory phenotype, as we already have demonstrated (8), which can be independent of LCMV infection.…”
Section: Discussionmentioning
confidence: 51%
“…Normally, CD8 T cells in WT mice expand to reach a peak burst size at day 8, after which they enter a decay phase after complete clearance of the virus (27), whereas in the KO mice the defects in activation and proliferation of cytotoxic cells may delay viral clearance, which might explain a higher proportion of residual effector cells in the lymph nodes, in contrast to WT mice. Additionally, it has also been reported that MLN T cells could present abnormal phenotypes under viral infection (28). Is also important to remark that Srsf1-cKO mice have a disrupted naïve to effector/ effector memory phenotype, as we already have demonstrated (8), which can be independent of LCMV infection.…”
Section: Discussionmentioning
confidence: 51%